Exploring Translation Strategies of Japanese Manga in Google Translate and Komikcast Translations - Yusof, Badriyah; Basuni, Hassanal (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This paper examines the translations of ‘Golden Kamuy Vol. 1’ from Japanese to Bahasa Melayu/Bahasa Indonesia by MT system Google Translate (GT) and online fan-based translating community Komikcast. Given the linguistic and sociocultural differences between the source language (SL) and target language (TL), translating manga demands expertise and a profound understanding of the cultural nuances embedded in the SL, the specific manga genre, and the target audience. This qualitative descriptive study uses Vinay and Darbelnet’s (1958/1995) translation strategies to analyze the translations of ‘Golden Kamuy Vol. 1’ by GT and Komikcast. The study finds that both platforms employ Literal Translation, Borrowing, and Equivalence strategies, with Komikcast additionally using Modulation. GT primarily relies on literary translation, which is consistent with its algorithmic nature and reliance on translation memories. Conversely, Komikcast emphasizes the Equivalence strategy, recognizing the significance of language proficiency and the contextual and cultural insights human translators provide. Findings are discussed in relation to Nida’s equivalence effects, particularly regarding the translated text’s purpose, translators’ knowledge, and cultural differences in SL and TL. This research enhances our understanding of manga translation, as well as the strengths and limitations of machine and human translation, while contributing to the broader discussion on translation studies. While acknowledging the role and potential of machine translation, this research also reinforces the critical role of human translators in bridging linguistic and cultural gaps between Japanese and Indonesian, highlighting the need for translators to possess deep cultural insights and proficiency beyond literal translations for more authentic and contextually accurate renditions.